2022
DOI: 10.3390/f13101609
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota Associated with Symptomatic and Asymptomatic Fraxinus excelsior in Post-Dieback Forest Stands

Abstract: In Lithuania, the dieback of European ash (Fraxinus excelsior L.), caused by alien ascomycete Hymenoscyphus fraxineus, started in the mid-1990s, resulting in a large-scale decline of F. excelsior and its dominated forest habitats. Nevertheless, the recent inventories show the presence of several hundred hectares of naturally regenerated F. excelsior stands. We used seven naturally regenerated sites and three planted progeny trials of F. excelsior to collect leaves, shoots, roots, and the surrounding soil to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Cladosporium sp. (inhibition factor 76%) was relatively infrequently isolated in the present study ( Table 2 ), but it was among the dominating fungi in a high-throughput sequencing study [ 15 ], therefore this particular fungal taxon can be regarded as frequent in nature.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Cladosporium sp. (inhibition factor 76%) was relatively infrequently isolated in the present study ( Table 2 ), but it was among the dominating fungi in a high-throughput sequencing study [ 15 ], therefore this particular fungal taxon can be regarded as frequent in nature.…”
Section: Resultsmentioning
confidence: 92%
“…The fungal taxa detected in shoots and leaves of F. excelsior were similar to those reported in numerous other culture-based studies [ 11 , 12 , 13 , 14 ]. However, high-throughput sequencing of the shoot and leave samples collected in the present study revealed a very contrasting fungal community structure [ 15 ]. Evidently, each of the aforementioned fungal detection methods has its advantages and shortcomings, suggesting that the use of both methods can provide valuable complementary information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation